2018
DOI: 10.1080/17434440.2018.1431121
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and repeatability of the Dopplex Ability

Abstract: We found the Dopplex device to demonstrate suboptimal accuracy and repeatability in assessing ABI/PVR, and it was deemed unsuitable for use in our community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…For air plethysmography, all of the identified studies analyzed the same model of the device ( Table 3 ). Millen et al found that the device showed accuracy and repeatability at suboptimal levels [ 45 ], while van der Slegt et al pointed to higher ABI values obtained with plethysmography and described the device as not applicable clinically [ 46 ]. Babaei et al described air plethysmography specificity as excellent, along with the specificity of Doppler ABI and pulse volume waveform assessment; however, the sensitivity of plethysmography was the lowest of the three methods analyzed [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For air plethysmography, all of the identified studies analyzed the same model of the device ( Table 3 ). Millen et al found that the device showed accuracy and repeatability at suboptimal levels [ 45 ], while van der Slegt et al pointed to higher ABI values obtained with plethysmography and described the device as not applicable clinically [ 46 ]. Babaei et al described air plethysmography specificity as excellent, along with the specificity of Doppler ABI and pulse volume waveform assessment; however, the sensitivity of plethysmography was the lowest of the three methods analyzed [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies that included PVR assessment apart from ABI measurement, found that component to be more diagnostically accurate than ABI measurement alone [ 36 , 38 , 45 ]. Lewis et al concluded that combining both methods is a highly accurate PAD exclusion modality [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies [12, 4751, 55, 57] included only participants with suspected PAD, or risk factors for atherosclerosis; three studied a mixed population including those without risk factors or clinical indicators of PAD [13, 16, 52]; two studies included only participants with diabetes [53, 54], and two studies included only healthy individuals [46, 56].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies did not state the number of limbs included [52, 53]. Eleven studies assessed inter‐rater reliability [12, 13, 16, 46–50, 56, 57], and eight studies reported intra‐rater reliability [13, 16, 52–57]. The characteristics of included studies are described in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation